Management Indicators - Santos Jiménez, Néstor (2000)
Investors and shareholders of companies require dindicadores which to judge the evolution, current situation and prospects of the operational, financial and economic performance of the business assets that have committed their capital. these indicators, which are indices or values ​​that relate the various activities of the organization, allow management apreciart if the company allows it to carry satisfatoria way of the demands of their customers, so as to ensure the sustainable in neocio time, thus ensuring the recovery of investor capital with a return or proper return, as the context in which the company operates.